Employee Stock Ownership - Simon Torp (Copenhagen Business School (CBS), 2011)
This dissertation creates a model that combines the literature on employee stock ownership (ESO), middle management involvement in strategy and the participative leader ship style with the motivational literature on psychological owners hip. The model is based on the recognition that despite a strong theoretical foundation of the firs t three concepts supporting a positive relationship with performance, the empirical evidence is inconclusive. Additiona lly, the literature on the three concepts finds that the performance effect of the concepts seems to be me diated by the creation of internalised extrinsic motiva tion in the form of psychologi cal empowerment, organisational citizenship behaviour or psyc hological ownership. Based on th e literature on psychological ownership, ESO, middle management involvement and a participative leadership style are argued to be determinants of psychological ownership. The m odel thereby argues that the three concepts must be seen as determinants of psychological owners hip and that their pote ntial positive effect on performance is triggered by their potential motivationa l effect. The three concepts can also be seen as interrelated and the model argues that a combin ation of the three would enhance the performance effect.
hdl:10398/8292
Keywords: 650